TECHNOLOGICAL AND REGENERATIVE INNOVATIONS IN THE MANAGEMENT OF INTERSTITIAL CYSTITIS/BLADDER PAIN SYNDROME (IC/BPS): AN INTEGRATIVE REVIEW OF INTRAVESICAL AND CELLULAR THERAPIES - Łysak, Kinga; Fimiarz, Kornelia Julia; Grygutis, Irmina; Pawełkiewicz, Sonia; Pyż, Iga; Łęczycka, Anna; Łysak, Iga (International Journal of Innovative Technologies in Social Science, 2026)
Background: Interstitial Cystitis/Bladder Pain Syndrome (IC/BPS) is a chronic inflammatory disorder characterized by urothelial barrier disruption, pelvic pain, urinary urgency and frequency, and significant psychosocial burden.  This condition represents a significant therapeutic challenge due to urothelial barrier dysfunction and the “washout effect,” which drastically shortens the exposure time of intravesically administered drugs.Objectives: This review aims to comprehensively analyze recent (2020–2026) advances in regenerative and nanotechnological approaches designed to overcome traditional limitations in IC/BPS treatment. Emphasis is placed on evaluating the clinical efficacy, biological mechanisms, and social impact of next-generation therapies.Methodology: A literature search was performed in PubMed, Scopus, MEDLINE, and Google Scholar for publications from 2020 to 2026 related to IC/BPS, focusing on thermosensitive hydrogels, nanocarriers, Platelet-Rich Plasma (PRP), amniotic-derived products, and gene-modulating therapies. Only peer‑reviewed preclinical and clinical research relevant to innovative IC/BPS management was analyzed.Results: Regenerative interventions, including Platelet-Rich Plasma (PRP) and Amniotic Bladder Therapy (ABT), demonstrate clinical symptom relief and improved Global Response Assessment (GRA) scores for up to 6 months. Network meta-analysis identifies PRP as highly effective for pain reduction ($SMD = -1.84$) compared to standard instillations. Advanced Drug Delivery Systems (DDS), such as thermosensitive hydrogels, extend intravesical drug residence to 5–7 days in preclinical models. Molecular precision therapies, specifically antisense Nerve Growth Factor (NGF) inhibitors and c-Jun N-terminal kinase (JNK) blockers, enable targeted intracellular modulation of neurogenic inflammation.Conclusion: The transition from palliative barrier substitution to biohybrid platforms integrating sustained drug delivery with regenerative signaling represents the current therapeutic paradigm. Future implementation requires standardized clinical protocols and large-scale randomized trials to address existing translational gaps.